2017
DOI: 10.2134/jeq2016.10.0399
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Scanning Transmission X‐Ray Microscopy for Elucidating Soil Biogeochemical Processes at the Submicron Scale

Abstract: Organic matter, minerals, and microorganisms are spatially associated in complex organo-mineral assemblages within soils. A mechanistic understanding of processes occurring within organo-mineral assemblages requires noninvasive techniques that minimize any disturbance to the physical and chemical integrity of the sample. Synchrotron-based soft (50-2200 eV) X-ray spectromicroscopic techniques, including scanning transmission X-ray microscopy (STXM), transmission X-ray microscopy (TXM), X-ray photoemission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are widely used to obtain information on the arrangement of organo‐mineral associations. Although both of those two approaches are not species sensitive, when coupled to electron‐dispersive X‐ray microscopy or electron energy loss spectroscopy (EELS), these techniques can be used to identify mineral species and/or metal valance ratios, as discussed by Stuckey et al (2017) in this issue. Scanning transmission X‐ray microscopy is a powerful SR‐based technique that uses soft, high‐flux X‐ray photons to map micrometer‐sized environmental samples with nanometer spatial resolution (Jacobsen et al, 2000).…”
Section: Summaries Of Papers In This Special Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) are widely used to obtain information on the arrangement of organo‐mineral associations. Although both of those two approaches are not species sensitive, when coupled to electron‐dispersive X‐ray microscopy or electron energy loss spectroscopy (EELS), these techniques can be used to identify mineral species and/or metal valance ratios, as discussed by Stuckey et al (2017) in this issue. Scanning transmission X‐ray microscopy is a powerful SR‐based technique that uses soft, high‐flux X‐ray photons to map micrometer‐sized environmental samples with nanometer spatial resolution (Jacobsen et al, 2000).…”
Section: Summaries Of Papers In This Special Sectionmentioning
confidence: 99%
“…When STXM is coupled with NEXAFS (STXM‐NEXAFS spectromicroscopy), it can be used for spectral fingerprinting of fine structures. This approach has contributed to the greatest set of advancements in the understanding of soil organo‐mineral interactions in recent years (Stuckey et al, 2017). …”
Section: Summaries Of Papers In This Special Sectionmentioning
confidence: 99%
“…Since synchrotron-based X-ray microscopes offer continuously tunable excitation photon energy, it has been shown that within a multilayer of several photoresists consecutively stacked at the same spot, each layer can be addressed separately by the resonant photon energy of the respective Following the development of suitable focusing optics for soft X-rays [49][50][51], the first soft X-ray microscopes were installed in the mid-1980s [52,53]. Since then, STXM has developed into a versatile method for characterization of suitably thin specimens from various scientific disciplines, such as biology, medicine, catalysis, material science, magnetism, geology, cosmology, and cultural heritage [54][55][56][57][58][59][60][61][62][63][64]. Figure 1 depicts a scheme of a modern STXM with all basic elements and their respective degrees of freedom [59,65,66].…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, methods operating at the micrometer scale such as electron‐microprobe analysis (EMPA) or scanning‐electron microscopy (SEM) with energy‐dispersive X‐ray spectroscopy (EDX) have been applied, although individual particles may be present, which are tens to hundreds of nanometers in size. Identifying these particles requires methods operating at the appropriate spatial scale, e.g., transmission‐electron microscopy on samples prepared with a focused ion beam or synchrotron radiation‐based X‐ray spectromicroscopy . Spatially resolved data (maps) obtained by X‐ray spectromicroscopy have been evaluated by image difference, correlation analysis, and principal component analysis‐cluster analysis .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Spatially resolved data (maps) obtained by X-ray spectromicroscopy have been evaluated by image difference, correlation analysis, and principal component analysis-cluster analysis. 5,6 Also nano-scale secondary ion mass spectrometry (NanoSIMS) might be an alternative, because its lateral resolution ranges from 50 to 150 nm, and it provides the spatial distribution of ion signals. 7 Thus, like X-ray spectromicroscopic data, NanoSIMS measurements may be similarly evaluated by image analysis to infer the distribution and speciation of elements and species.…”
Section: Introductionmentioning
confidence: 99%